From batch to continuous: Au-catalysed oxidation of d-galacturonic acid in a packed bed plug flow reactor under alkaline conditions. Issue 4 (18th June 2018) - van der Klis, F.; Gootjes, L.; van Haveren, J.; van Es, D. S.; Bitter, J. H.
Abstract : Comparing the Au-catalysed oxidation of sugar acids: highest selectivity obtained in batch, superior productivity in flow. Abstract : Currently biomass based conversions are often performed in batch reactors. From an operational and economic point of view the use of a continuous plug flow reactor is preferred. Here we make a back to back comparison of the use of a batch and plug flow reactor for the oxidation of (sodium)-galacturonate to (disodium)-galactarate using a heterogeneous Au-catalyst. We will show that the use of a three phase plug flow reactor results in enhanced O2 mass transfer which resulted in a 10–40 fold increase in productivity (up to 2.2 ton m −3 h −1 ). However, the product selectivity slightly dropped from >99 mol% in batch (controlled pH) to 94 mol% in packed bed (uncontrolled pH). Both reactors suffer from the low solubility of the reaction product. We will show that this solubility is the most significant challenge for performing this oxidation on industrial scale.